Prognosis for ocular toxocariasis according to granuloma location - Kwon, Jin-woo (PLoS One, 2018)
PURPOSE: To determine the prognosis for ocular toxocariasis (OT) according to the location of the granuloma and to identify factors associated with its recurrence within 1 year. METHODS: OT patients were classified according to the granuloma lesion. After grouping the patients as posterior or peripheral, we compared sex, age, intraocular pressure, best corrected visual acuity (BCVA), degree of inflammation, immunoglobulin E, eosinophil profiles, recurrence, and complications in each group. We also identified factors associated with recurrence within 1 year. RESULTS: A total of 29 (61.70%) patients had granuloma at the periphery, and 18 (38.30%) patients had granuloma around the posterior pole. There were no significant differences in ocular or systemic evaluations except the initial BCVA. The mean decimal BCVA of the posterior pole granuloma group was worse than that of the peripheral granuloma group (p = 0.042). After treatment, the mean BCVA of the posterior pole granuloma group improved significantly (p = 0.019), and the final mean BCVA was not significantly different between the groups (p = 0.673). Multiple logistic regression analyses revealed that recurrence within a year was associated with age at diagnosis (p = 0.007). CONCLUSIONS: The initial BCVA of OT patients differed according to the location of the granuloma, but the BCVA after treatment was not significantly different between the groups. Younger age was associated with recurrence within 1 year.